In the land of invented languages : Esperanto rock stars, Klingon poets, Loglan lovers, and the mad dreamers who tried to build a perfect language - Okrent, Arika (New York : Spiegel & Grau, 2009)
Okrent tells the fascinating and highly entertaining history of man's enduring quest to build a better language. Peopled with charming eccentrics and exasperating megalomaniacs, the land of invented languages is a place where you can recite the Lord's Prayer in John Wilkins's Philosophical Language, say your wedding vows in Loglan, and read "Alice's Adventures in Wonderland" in Lojban--not to mention Babm, Blissymbolics, and the nearly nine hundred other invented languages featured in this language-lover's book.
Nine hundred languages, nine hundred years ; John Wilkins and the language of truth ; Ludwik Zambof and the language of peace ; Charles Bliss and the language of symbols ; James Cooke Brown and the language of logic ; The Klingons, the Conlangers, and the art of language.
Includes bibliogr. references (p. [323]-329) and index.
Keywords: Languages, Artificial; Esperanto; Klingon (Artificial language); Blissymbolics; Lojban (Artificial language); Loglan (Artificial language)